AfsK-Mediated Site-Specific Phosphorylation Regulates DnaA Initiator Protein Activity in Streptomyces coelicolor - Łebkowski, Tomasz (J Bacteriol, 2020)
In all organisms, chromosome replication is regulated mainly at the initiation step. Most of the knowledge about the mechanisms that regulate replication initiation in bacteria has come from studies on rod-shaped bacteria, such as Escherichia coli and Bacillus subtilis. Streptomyces is a bacterial genus that is characterized by distinctive features and a complex life cycle that shares some properties with the developmental cycle of filamentous fungi. The unusual lifestyle of streptomycetes suggests that these bacteria use various mechanisms to control key cellular processes. Here, we provide the first insights into the phosphorylation of the bacterial replication initiator protein, DnaA, from Streptomyces coelicolor. We suggest that phosphorylation of DnaA triggers a conformational change that increases its ATPase activity and decreases its affinity for the replication origin, thereby blocking the formation of a functional orisome. We suggest that the phosphorylation of DnaA is catalyzed by Ser/Thr kinase AfsK, which was shown to regulate the polar growth of S. coelicolor. Together, our results reveal that phosphorylation of the DnaA initiator protein functions as a negative regulatory mechanism to control the initiation of chromosome replication in a manner that presumably depends on the cellular localization of the protein. IMPORTANCE This work provides insights into the phosphorylation of the DnaA initiator protein in Streptomyces coelicolor and suggests a novel bacterial regulatory mechanism for initiation of chromosome replication. Although phosphorylation of DnaA has been reported earlier, its biological role was unknown. This work shows that upon phosphorylation, the cooperative binding of the replication origin by DnaA may be disturbed. We found that AfsK kinase is responsible for phosphorylation of DnaA. Upon upregulation of AfsK, chromosome replication occurred further from the hyphal tip. Orthologs of AfsK are exclusively found in mycelial actinomycetes that are related to Streptomyces and exhibit a complex life cycle. We propose that the AfsK-mediated regulatory pathway serves as a nonessential, energy-saving mechanism in S. coelicolor.